Utility of magnetic anomaly data collected from different platforms - Anand, S. P.; Rajaram, M. (My University, 2009)
Technological advancement in the past two decades coupled with better acquisition, processing and interpretation techniques have made the magnetic method an important tool for exploration. The information content provided by magnetic surveys ranges from global to very detailed scales depending on the survey platform and resolution. At the Indian Institute of Geomagnetism in addition to conducting ground surveys, we have extensively utilized aero, satellite and marine magnetic data for unraveling the tectonics, geothermal and geodynamic history of the Indian sub-continent.
Keywords: Magnetic anomaly data; Mineral resources; Magnetic surveys; Ground surveys